ChemInform Abstract: Donor—Acceptor Bonding in Novel Low‐Coordinated Compounds of Boron and Group‐14 Atoms C—Sn. Issue 15 (24th March 2016) - Frenking, Gernot; Hermann, Markus; Andrada, Diego M.; Holzmann, Nicole
Abstract: Review: [85 refs.